FEATURES OF CONDUCT OF SOME INVESTIGATIVE (SEARCH) ACTIONS UNDER THE CONDITIONS OF THE STATE OF MARTIAL - Litvinova, Iryna; Malykhina, Alina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: using the criminal procedural legislation of Ukraine, to conduct an analysis of some types of investigative (search) actions and to find out the peculiarities of their conduct in the conditions of martial law. Research methods: abstract-logical, comparativelegal, analytical and special-legal methods, in particular formal-legal and formal-logical methods. Results: some investigative (research) actions considered in the article are aimed at identifying, recording and evaluating evidence both in wartime and peacetime conditions. They are also important for establishing the circumstances of committing a criminal offense. Some of these actions cannot be carried out in accordance with the general conditions defined by the CPC, therefore a simplified procedure applies to them. Despite this, the legislator still needs to fully adapt the legal framework in accordance with the effect of the special regime and the realities of today. Іt was established that investigative (search) actions are a significant tool of evidence in criminal proceedings. It is proposed to adapt the regulatory and legal framework in the field of investigative (search) actions in accordance with the conditions of martial law. Discussion: procedural aspects of conducting some investigative (search) actions and characteristics of each of them. Currently, there is an urgent problem of bringing into compliance with the conditions of the special regime of actions aimed at obtaining and verifying evidence in criminal proceedings. Investigative (search) actions are an important element in criminal proceedings, the task of which is to identify, record and verify evidence. How well the investigation will be conducted and how fair the court verdict will be depends on how precisely the requirements of the criminal procedure and other special legislation will be observed. Taking into account the fact that martial law has been imposed on the territory of Ukraine, investigative (search) actions as a method of evaluating evidence have undergone significant changes and their implementation has become somewhat more difficult. Abuse by law enforcement and other bodies, violation of human and citizen rights and freedoms are not the only problems that each of us can face. Therefore, today, it is extremely relevant and important to find out and determine the specifics of conducting some investigative (search) actions in the conditions of martial law.